RELASI NILAI NASIONALISME DAN KONSEP HUBBUL WATHAN MINAL IMAN DALAM PENDIDIKAN ISLAM - Ibda, Hamidulloh (International Journal Ihya' 'Ulum al-Din, 2017)
This article aims to find out the concept of hubbul wathan minal imanand nationalism in Islamic education. It also describes the genealogy of nationalism and hubbul wathan minal iman, the dynamics of the anti-nationalism group, and the character of nationalism in Islamic education. The findings in this article indicate the character of nationalism is very influential on the resilience of the nation, one of them through the program strengthening character education established by the government. In that program, there is a character of the spirit of nationalism and love of the homeland as a form of hubbul wathan minal iman that can be applied by all Islamic educational institutions to maintain the spirit of nationalism.Artikel ini bertujuan untuk mengetahui konsep hubbul wathan minal iman dan nasionalisme dalam pendidikan Islam. Selain itu juga mendeskripsikan genealogi nasionalisme dan hubbul wathan minal iman, dinamika kelompok antinasionalisme, dan karakter nasionalisme dalam pendidikan Islam. Temuan dalam artikel ini menunjukkan karakter nasionalisme sangat berpengaruh terhadap ketahanan bangsa, salah satunyamelalui program Penguatan Pendidikan Karakter (PPK) yang ditetapkan pemerintah. Dalam progam itu, terdapat karakter semangat kebangsaan dan cinta tanah air sebagai wujud hubbul wathan minal iman yang bisa diterapkan semua lembaga pendidikan Islam untuk menjaga ruh nasionalisme.